The behavior of minors and road safety – case study of Poland - Wrona Rafał; Rybicka Iwona Katarzyna; Stoma Monika (Open Engineering)
The article examines traffic safety and incidents involving children and underage drivers. It discusses legal regulations for pedestrians, underage drivers, and vehicle operators, highlighting the causes and consequences of accidents involving minors on single-track vehicles. Four examples of such accidents are analyzed, with photographs provided for evidence. The analysis focuses on identifying causes and exploring prevention strategies. The findings suggest the need for measures to enhance road safety, particularly for young users, and emphasize the importance of further research to address the tragic outcomes of these incidents.